THE EFFECT OF MULTIPLE REPRESENTATIONS IN TEACHING MATHEMATICAL CONCEPTS IN MATHEMATICS LITERACY AMONG INTERMEDIATE LEVEL STUDENTS - Meeaad Jasim Salman Al-Sarry (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The aim of the research is to know the effect of using multiple representation in the Mathematics Literacy of female students in the first intermediate class, and to achieve the goal of the research, the experimental approach was adopted and the design of equivalence groups with dimensional testing of the two groups (experimental and control) was chosen. A random sample was chosen consisting of (57) female students from the first intermediate class, by (32) students for the experimental group that studied mathematics according to multiple representation, and (25) students for the control group that studied mathematics according to the usual way, parity was conducted between two groups in the variables (intelligence, chronological age, previous achievement in mathematics, Mathematics Literacy). In addition, Mathematics Literacy test was constructed of (27) items divided into three axes (concepts, principles and basic skills- mathematical thinking- the nature of mathematics and the history of its development). The test was applied at the end of the experiment to the two groups of the study sample and after statistically processing the results; it was found that there was a statistically significant difference in favor of the experimental group in the Mathematics Literacy as a whole and in each of its axes. Key words: Multiple Representation, Mathematics Literacy.